The Effect of Work Environment, Work Ethics, Work Motivation and Work Discipline on Performance - Wahyu Hidayat; Antony Setiawan; Shella Meylani; Rangga Adhitia Hermawan (Lafadz Jaya Publisher, 2025)
Human resource (HR) development in every company is important to realize the improvement of HR quality in various aspects. Employee performance is often the focus of research in the field of HR because it has a crucial role in improving the company's work system. Some factors that affect employee performance include work discipline, work ethics, work motivation, and work environment. This study aims to analyze the influence of these factors on employee performance. This study uses an associative approach, which examines the relationship between two variables. The research sample consisted of 188 employees of PT Asuransi Reliance Indonesia, who were selected using the Slovin formula from a population of 347 employees. The results showed that the work environment had no partial effect on performance, while work ethics, work motivation, and work discipline had a partial effect on performance. Simultaneously, the four factors affect employee performance. This study provides recommendations for future research to consider other variables that have not been studied, either as moderating or intervening variables, to deepen understanding of the influence of the work environment on performance.